Development of an Educational Model for Taḥfīẓ al-Qur´ān Based on the "asy-Syakhṣiyyah al-Mujāhidah" for University Students: تطوير النموذج التعليمي لتحفيظ القرآن على أساس "الشخصية المجاهدة" لطلاب الجامعة - Hadil Ismail Hasan; Abas Mansur Tamam; Akhmad Alim; Ahmad Abdel Hady (ZAD Al-Mufassirin, 2026)
Current Qur'an memorization (tahfidz) practices in higher education urgently require reconstruction because the dominance of a quantitative orientation often neglects character building, thereby producing memorizers who are psychologically vulnerable and lack self-regulation. This study aims to develop and test the feasibility of the "Mujahid Character-Based Qur'an Tahfidz Educational Model" as an integrated curriculum for university students. This research employs the Research and Development (R&D) method based on the ADDIE (Analysis, Design, Development) model, utilizing questionnaires, Focus Group Discussions (FGD), and expert validation (Expert Judgment). The results formulated the "MUJAHID" learning syntax, which translates character into four operational dimensions: resilience, discipline, courage, and patience. This model is supported by a comprehensive evaluation system that integrates memorization mastery (mutqin) with character development. The feasibility test by experts yielded a "very good" rating (score 4.0–4.44), confirming the model's high conceptual validity and operational readiness. The novelty of this research lies in reconstructing the tahfidz concept from mere mechanical rote learning into an objectively measurable process of spiritual leadership transformation. Regarding policy implications, this study recommends that higher education administrators restructure tahfidz programs from mere extracurricular activities into official curriculum standards that integrate academic evaluation with student character building.